Full Field Strain Measurements Uncover the Influence of External Far-Field Stresses on Fracturing During Cavity Expansion in Anisotropic Sandstone - Manab Mukherjee; Yves Méheust; Pascal Charrier; Pierre Bésuelle (Rock Mechanics and Rock Engineering, 2026)

Clinical spectrum of ICU-acquired invasive pulmonary aspergillosis according to SARS-CoV2 infection: a multicenter prospective cohort study - Florian Reizine; Mattéo Mauget; Nicolas Massart; Yannick Fedun; Anaïs Machut; Charles-Hervé Vacheron; Anne Savey; Arnaud Friggeri; Alain Lepape; Melissa Abbes; Abdelkrim Abdelmalek; Francoise Adema; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2026)

Importance of the microphytobenthos in the foodweb of tropical mudflats - Alexandre Carpentier; Anne Lizé; Hien Nguyen Thanh; Pierrick Bocher; Christel Lefrançois; Antoine Gardel; Pierre-Yves Pascal; Christine Dupuy (Estuarine, Coastal and Shelf Science, 2025)

The Late Pleistocene - Holocene meandering lower Garonne River, southwest France: Architecture of the valley fill and chronology, comparison with other European rivers - Pascal Bertran; Eric Andrieux; Sophie Leleu; Zoe Sicard-Delage; Benjamin Fores; Rachid Ouchaou; Pierre Weill; Jean-Yves Reynaud (Geomorphology, 2025)

The i-FSC proxy for predicting inter-event and spatial variation of topographic site effects - Aline Bou Nassif; Emeline Maufroy; Pascal Lacroix; Emmanuel Chaljub; Mathieu Causse; Pierre-Yves Bard (Bulletin of Earthquake Engineering, 2025)
Our study focuses on predicting topographic amplification of ground motion in the near-source region, where seismic rays reach the free-surface at varying incidence angles. We rely on data from previous 3D numerical simulations conducted on a topographic relief with a homogeneous medium. First, using neural networks, we identify which key parameters, describing the geometric characteristics of the relief relative to the seismic source position, control ground motion amplification. Then, we determine the functional form that relates these parameters to the simulated amplifications. Subsequently, we conduct a regression study to develop a model of topographic amplification, referred to as the i-FSC proxy (Illuminated Frequency-Scaled Curvature). Our estimator depends on the frequency-scaled (1) curvature, a parameter that accounts for the occurrence of amplifications over convex topographies and de-amplification over concave ones; (2) normalized illumination angle, a newly defined parameter that quantifies the slope exposure to the incoming wavefield, accounting for high amplification on slopes oriented opposite to the seismic source. The illumination parameter reduces the uncertainties of the proxy by a factor of 2 compared to estimators that rely solely on curvature. The proxy does not require high computational resources. It uses a digital elevation map and a seismic source position to predict amplification factors (without lithological effects) for an S -wave at any site on the surface topography. It allows exploration of variations in topographic amplification near seismic sources, representing a significant breakthrough as areas closest to the fault typically sustain the highest damages. A MATLAB script performing the i-FSC calculations is provided.

Mercury Accumulation and Transfer in Hydrothermal Coastal Environment: The Case of the Geothermal Plant of Bouillante - Eliot Ruiz; Thomas Lacoue-Labarthe; Carine Churlaud; Maud Brault-Favrou; Pierre-Yves Pascal (Archives of Environmental Contamination and Toxicology, 2024)

Seasonal variation in biochemical and metal content of the invasive seaweed Sargassum muticum along Moroccan Atlantic Coast - Abderrahmane Aamiri; Nor-Eddine Rezzoum; Yasmine Touhamia; Hakima Zidane; Lhoucine Benhassan; Pierre-Yves Pascal; Touria Ould Bel lahcen (Journal of Applied Phycology, 2024)

Temporal fluctuation of metallic trace elements concentrations in three morphotypes of floating holopelagic Sargassum from the Caribbean coast (Guadeloupe, French West Indies) - Océanne-Amaya Cipolloni; Patrice Couture; Sébastien Cordonnier; Pierre-Yves Pascal (Marine Pollution Bulletin, 2024)

Estimating urban seismic damages and debris from building-level simulations: application to the city of Beirut, Lebanon - Rouba Iskandar; Bilal Al Tfaily; Cécile Cornou; Pierre-Yves Bard; Bertrand Guillier; Jacques Harb; Pascal Lacroix; Jocelyne Adjizian-Gérard; Elise Beck; Julie Dugdale; Christelle Salameh; Nada Saliba; et al. (Bulletin of Earthquake Engineering, 2023)

Kinetics of metal and metalloid concentrations in holopelagic Sargassum reaching coastal environments - Océanne-Amaya Cipolloni; Magalie Baudrimont; Benoît Simon-Bouhet; Émilie Pauline Dassié; Julien Gigault; Solène Connan; Pierre-Yves Pascal (Environmental Science and Pollution Research, 2023)

Cover crop response to increased concentrations of copper in vineyard soils: Implications for copper phytoextraction - Pierre Eon; Thierry Robert; Jean-Pascal Goutouly; Violette Aurelle; Jean-Yves Cornu (Chemosphere, 2023)

First assessment of Atlantic open ocean Sargassum spp. metal and metalloid concentrations - Emilie Pauline Dassié; Pierre-Yves Gourves; Océanne Cipolloni; Pierre-Yves Pascal; Magalie Baudrimont (Environmental Science and Pollution Research, 2022)

Adaptive potential of Coffea canephora from Uganda in response to climate change - Sinara Oliveira de Aquino; Catherine Kiwuka; Rémi Tournebize; Clément Gain; Pierre Marraccini; Cédric Mariac; Kévin Bethune; Marie Couderc; Philippe Cubry; Alan C. Andrade; Maud Lepelley; Olivier Darracq; et al. (Molecular Ecology, 2022)
Understanding vulnerabilities of plant populations to climate change could help preserve their biodiversity and reveal new elite parents for future breeding programmes. To this end, landscape genomics is a useful approach for assessing putative adaptations to future climatic conditions, especially in long‐lived species such as trees. We conducted a population genomics study of 207 Coffea canephora trees from seven forests along different climate gradients in Uganda. For this, we sequenced 323 candidate genes involved in key metabolic and defence pathways in coffee. Seventy‐one single nucleotide polymorphisms (SNPs) were found to be significantly associated with bioclimatic variables, and were thereby considered as putatively adaptive loci. These SNPs were linked to key candidate genes, including transcription factors, like DREB ‐like and MYB family genes controlling plant responses to abiotic stresses, as well as other genes of organoleptic interest, such as the DXMT gene involved in caffeine biosynthesis and a putative pest repellent. These climate‐associated genetic markers were used to compute genetic offsets, predicting population responses to future climatic conditions based on local climate change forecasts. Using these measures of maladaptation to future conditions, substantial levels of genetic differentiation between present and future diversity were estimated for all populations and scenarios considered. The populations from the forests Zoka and Budongo, in the northernmost zone of Uganda, appeared to have the lowest genetic offsets under all predicted climate change patterns, while populations from Kalangala and Mabira, in the Lake Victoria region, exhibited the highest genetic offsets. The potential of these findings in terms of ex situ conservation strategies are discussed.

Ocean Integration: The Needs and Challenges of Effective Coordination Within the Ocean Observing System - Adèle Révelard; Joaquín Tintoré; Jacques Verron; Pierre Bahurel; John A. Barth; Mathieu Belbéoch; Jérôme Benveniste; Pascal Bonnefond; Eric P. Chassignet; Sophie Cravatte; Fraser Davidson; Brad deYoung; et al. (Frontiers in Marine Science, 2022)
Understanding and sustainably managing complex environments such as marine ecosystems benefits from an integrated approach to ensure that information about all relevant components and their interactions at multiple and nested spatiotemporal scales are considered. This information is based on a wide range of ocean observations using different systems and approaches. An integrated approach thus requires effective collaboration between areas of expertise in order to improve coordination at each step of the ocean observing value chain, from the design and deployment of multi-platform observations to their analysis and the delivery of products, sometimes through data assimilation in numerical models. Despite significant advances over the last two decades in more cooperation across the ocean observing activities, this integrated approach has not yet been fully realized. The ocean observing system still suffers from organizational silos due to independent and often disconnected initiatives, the strong and sometimes destructive competition across disciplines and among scientists, and the absence of a well-established overall governance framework. Here, we address the need for enhanced organizational integration among all the actors of ocean observing, focusing on the occidental systems. We advocate for a major evolution in the way we collaborate, calling for transformative scientific, cultural, behavioral, and management changes. This is timely because we now have the scientific and technical capabilities as well as urgent societal and political drivers. The ambition of the United Nations Decade of Ocean Science for Sustainable Development (2021–2030) and the various efforts to grow a sustainable ocean economy and effective ocean protection efforts all require a more integrated approach to ocean observing. After analyzing the barriers that currently prevent this full integration within the occidental systems, we suggest nine approaches for breaking down the silos and promoting better coordination and sharing. These recommendations are related to the organizational framework, the ocean science culture, the system of recognition and rewards, the data management system, the ocean governance structure, and the ocean observing drivers and funding. These reflections are intended to provide food for thought for further dialogue between all parties involved and trigger concrete actions to foster a real transformational change in ocean observing.

Feeding in spatangoids: the case of Abatus Cordatus in the Kerguelen Islands (Southern Ocean) - Pierre-Yves Pascal; Yann Reynaud; Elie Poulin; Chantal De Ridder; Thomas Saucede (Polar Biology, 2021)

Meiofauna versus macrofauna as a food resource in a tropical intertidal mudflat - Pierre-Yves Pascal; Pierrick Bocher; Christel Lefrançois; Hien T. Nguyen; Johan Chevalier; Christine Dupuy (Marine Biology, 2019)

Pan‐tropical prediction of forest structure from the largest trees - Jean‐François Bastin; Ervan Rutishauser; James R. Kellner; Sassan Saatchi; Raphael Pélissier; Bruno Hérault; Ferry Slik; Jan Bogaert; Charles De Cannière; Andrew R. Marshall; John Poulsen; Patricia Alvarez‐Loyayza; et al. (Global Ecology and Biogeography, 2018)
Aim Large tropical trees form the interface between ground and airborne observations, offering a unique opportunity to capture forest properties remotely and to investigate their variations on broad scales. However, despite rapid development of metrics to characterize the forest canopy from remotely sensed data, a gap remains between aerial and field inventories. To close this gap, we propose a new pan‐tropical model to predict plot‐level forest structure properties and biomass from only the largest trees. Location Pan‐tropical. Time period Early 21st century. Major taxa studied Woody plants. Methods Using a dataset of 867 plots distributed among 118 sites across the tropics, we tested the prediction of the quadratic mean diameter, basal area, Lorey's height, community wood density and aboveground biomass (AGB) from the i th largest trees. Results Measuring the largest trees in tropical forests enables unbiased predictions of plot‐ and site‐level forest structure. The 20 largest trees per hectare predicted quadratic mean diameter, basal area, Lorey's height, community wood density and AGB with 12, 16, 4, 4 and 17.7% of relative error, respectively. Most of the remaining error in biomass prediction is driven by differences in the proportion of total biomass held in medium‐sized trees (50–70 cm diameter at breast height), which shows some continental dependency, with American tropical forests presenting the highest proportion of total biomass in these intermediate‐diameter classes relative to other continents. Main conclusions Our approach provides new information on tropical forest structure and can be used to generate accurate field estimates of tropical forest carbon stocks to support the calibration and validation of current and forthcoming space missions. It will reduce the cost of field inventories and contribute to scientific understanding of tropical forest ecosystems and response to climate change.

Relocations and one-time disturbance fail to sustainably disperse non-breeding common ravens Corvus corax due to homing behaviour and extensive home ranges - Pascal Marchand; Matthias-Claudio Loretto; Pierre-Yves Henry; Olivier Duriez; Frédéric Jiguet; Thomas Bugnyar; Christian Itty (European Journal of Wildlife Research, 2018)

Atlas-Based Automatic Generation of Subject-Specific Finite Element Tongue Meshes - Ahmad Bijar; Pierre-Yves Rohan; Pascal Perrier; Yohan Payan (Annals of Biomedical Engineering, 2016)

Evaluating the genetic effects of the invasive O cenebra inornata on the native oyster drill O cenebra erinacea - Eric Pante; Pierre‐Yves Pascal; Vanessa Becquet; Amélia Viricel; Benoit Simon‐Bouhet; Pascale Garcia (Marine Ecology, 2015)
Studies focusing on the effect of invasive species on the genetic diversity of native marine invertebrates remain scant. Here we report diversity among French populations of the intertidal gastropod Ocenebra erinacea (Linnaeus, 1758) sampled in the presence and absence of the invasive Ocenebra inornata (Recluz, 1851). Between 1999 and 2004, a total of 352 individuals of O. erinacea was collected from 15 sites (five of which had the invasive present) and was genotyped at the mitochondrial locus Cytochrome Oxidase 1 ( cox1 ). No statistical difference was observed between polymorphism levels recorded within native populations exposed to the invasive, compared with populations sampled in the absence of O . inornata . No sign of native population decline was detected in response to the invader. While significant shifts in native O . erinacea population sizes have previously been reported in the literature, genetic effects may take longer to accumulate, or may be undetectable without a larger panel of genetic markers. By contrast, large genetic distances and significant population differentiation were recorded between Atlantic and Mediterranean O . erinacea samples, suggesting that these populations have distinct evolutionary histories. Comparison of genetic divergence within the closely related genus Nucella suggests that the Atlantic populations of O . erinacea and those from Thau Lagoon in the Mediterranean may belong to different species or subspecies.

Diet of Haplognathia ruberrima (Gnathostomulida) in a Caribbean marine mangrove - Pierre‐Yves Pascal; Claude Bellemare; Wolfgang Sterrer; Henricus T. S. Boschker; Silvina Gonzalez‐Rizzo; Olivier Gros (Marine Ecology, 2015)
Haplognathia ruberrima is a cosmopolitan gnathostomulid species found in sulfur bacterial mats in mangroves in Guadeloupe (French West Indies). Haplognathia ruberrima presents a δ 13 C value lower than all measured meiofaunal grazers and lower than the available measured food sources of this environment. This low δ 13 C value can not be due to specific ingestion of 13 C‐depleted methanogenic bacteria because abundances of those bacteria are reduced in surficial and deep sediments as revealed by δ 13 C of bacterial fatty acid. According to scanning electron microscope observations, no bacterial ectosymbionts were observed at the surface of the gnathostomulids, and transmission electron microscope views revealed the absence of bacterial endosymbionts. Energy‐dispersive X‐ray spectroscopy analysis detected low levels of sulfur (0.32%±0.8) in biological tissues of H. ruberrima , confirming the absence of thioautotrophic bacterial symbionts in these animals. Consequently, the low δ 13 C value of H. ruberrima can not be due to the presence of sulfur‐oxidizing symbionts but more probably to the selective and exclusive consumption of free‐living, sulfur‐oxidizing bacteria.

Diverse Dietary Responses by Saltmarsh Consumers to Chronic Nutrient Enrichment - Pierre-Yves Pascal; John W. Fleeger (Estuaries and Coasts, 2013)

Seasonal variability of cohesive sediment aggregation in the Bach Dang–Cam Estuary, Haiphong (Vietnam) - Jean-Pierre Lefebvre; Sylvain Ouillon; Vu Duy Vinh; Robert Arfi; Jean-Yves Panché; Xavier Mari; Chu Van Thuoc; Jean-Pascal Torréton (Geo-Marine Letters, 2012)

Uptake of a randomized breast cancer prevention trial comparing letrozole to placebo in BRCA1/2 mutations carriers: the LIBER trial - Pascal Pujol; Christine Lasset; Pascaline Berthet; Catherine Dugast; Suzette Delaloge; Jean-Pierre Fricker; Isabelle Tennevet; Nathalie Chabbert-Buffet; Pascale This; Karen Baudry; Jerome Lemonnier; Lise Roca; et al. (Familial Cancer, 2012)

Microarray-Based Identification of Gonad Transcripts Differentially Expressed Between Lines of Pacific Oyster Selected to Be Resistant or Susceptible to Summer Mortality - Elodie Fleury; Jeanne Moal; Viviane Boulo; Jean-Yves Daniel; David Mazurais; Alain Hénaut; Charlotte Corporeau; Pierre Boudry; Pascal Favrel; Arnaud Huvet (Marine Biotechnology, 2010)

Comparative analysis of reproductive traits in 65 freshwater fish species: application to the domestication of new fish species - Fabrice Teletchea; Alexis Fostier; Ewa Kamler; Jean-Noël Gardeur; Pierre-Yves Le Bail; Bernard Jalabert; Pascal Fontaine (Reviews in Fish Biology and Fisheries, 2009)

Harmonin-b, an actin-binding scaffold protein, is involved in the adaptation of mechanoelectrical transduction by sensory hair cells - Nicolas Michalski; Vincent Michel; Elisa Caberlotto; Gaelle M. Lefèvre; Alexander F. J. van Aken; Jean-Yves Tinevez; Emilie Bizard; Christophe Houbron; Dominique Weil; Jean-Pierre Hardelin; Guy P. Richardson; Corné J. Kros; et al. (Pflügers Archiv - European Journal of Physiology, 2009)

Seasonal variation in consumption of benthic bacteria by meio‐ and macrofauna in an intertidal mudflat - Pierre-Yves Pascal; Christine Dupuy; Pierre Richard; Clarisse Mallet; Eric Armynot du Châ telet; Nathalie Niquilb (Limnology and Oceanography, 2009)
The trophic fate of benthic bacteria in an intertidal mudflat (Brouage, Marennes‐Oléron, France) was evaluated in situ, and environmental parameters that potentially influence the consumption of bacteria by the most abundant organisms of the meio‐ and macrofauna were identified. Variations in grazing rates were estimated using 15 N pre‐enriched bacteria at different temporal and spatial scales on a cross‐shore transect over the mudflat. Grazing incubations were performed in microcosms with freshly collected grazers. Environmental factors varied more by season than by day or sampling station. Bacterial uptake by grazers did not appear to be strongly influenced by abiotic factors and was not linked to bacterial abundance. Algal abundance was negatively correlated with bacterivory in both the nematode community and the foraminifer Ammonia tepida , suggesting that bacteria constitute an alternative resource that is consumed when algae are less abundant. Bacteria were mainly ingested by the mudsnail Hydrobia ulvae and secondarily by nematodes with grazing rates of copepods and A. tepida being considerably lower. The estimated grazing in the upper and middle part of the mudflat represented 7% and 28% of bacterial production, respectively. In the lower mudflat, daily grazing never represented >3% of bacterial production throughout the year. Consequently, grazing appears to be a minor factor in the regulation of bacterial production. Bacterivory did not vary clearly according to season; consequently, the fate of bacteria in this benthic food web is poorly structured by season.

Bacterivory of a mudflat nematode community under different environmental conditions - Pierre-Yves Pascal; Christine Dupuy; Pierre Richard; Jadwiga Rzeznik-Orignac; Nathalie Niquil (Marine Biology, 2008)